(untitled) (East West Medical College Journal, 2026)
Background: Preeclampsia is a hypertensive disorder of pregnancy characterized by new-onset hypertension and proteinuria after 20 weeks of gestation. Although its exact pathophysiology remains incompletely understood, disturbances in essential micronutrients such as calcium, magnesium, and zinc have been implicated in disease development. Methods: This comparative cross-sectional study was conducted at Mymensingh Medical College and included 100 pregnant women (50 preeclamptic cases and 50 normotensive controls) selected using purposive sampling. Serum calcium, magnesium, and zinc levels were measured using standard colorimetric methods. Blood pressure was recorded, and statistical analyses were performed using SPSS version 25.0. Results: There were no significant differences in age (p = 0.963) or body mass index (p = 0.071) between the groups. Both systolic (142.79 ± 8.40 mmHg vs. 106.20 ± 6.96 mmHg) and diastolic blood pressure (93.62 ± 6.32 mmHg vs. 67.80 ± 5.82 mmHg) were significantly higher in preeclamptic women (p < 0.001). Serum calcium (7.78 ± 0.42 mg/dL vs. 9.07 ± 0.43 mg/dL), magnesium (1.37 ± 0.26 mg/dL vs. 1.88 ± 0.29 mg/dL), and zinc levels (42.12 ± 4.65 μg/dL vs. 92.82 ± 21.55 μg/dL) were significantly lower in the preeclamptic group (p < 0.001). Conclusion: Preeclamptic women exhibited significantly reduced serum calcium, magnesium, and zinc levels compared to normotensive pregnant women. These findings support a potential role of micronutrient imbalance in the pathogenesis of preeclampsia and underscore the need for further large-scale and interventional studies to evaluate the clinical benefits of targeted micronutrient monitoring and supplementation. EWMCJ Vol. 14, No. 2, July 2026: 162-169